LEXICAL COLLOCATION PRODUCTIVITY OF INDONESIAN L2 WRITERS IN ESSAY: A COMPARATIVE CORPUS-BASED STUDY - Yenni Arif Rahman (Universitas Majalengka, 2020)
The richness of collocation usage reflects the language mastery of English users. However, it has been recognized that L2 users often have problems with collocations due to several reasons. This study reports on lexical collocation productivity of Indonesian L2 writers to English-native writers in essays. The corpora were taken from 20 essays written by Indonesian L2 writers and English-native writers in English newspaper opinion column. To conduct the analysis, this study employed corpus-based comparative analysis suggested by Gonzales and Ramos. This is done by extracting all lexical collocation from the text by utilizing AntConc, a corpus analysis software. Then, collocations were sorted out from free combinations and collocation errors by using https://skell.sketchengine.eu, a reference corpora search-engine. The average use of lexical collocation of Indonesian L2 writers in essays was compared with lexical collocation of English-native writers. The results showed that Indonesian L2 writers is less productive than English-native writers in utilizing lexical collocation in their essays. Of the 4481 token in Indonesian L2 essays, there were 226 collocation in use or 50 collocations per 1000 token. That result was much lower than English-native collocation in essays which reports 80 collocations per 1000 token or 320 collocations of 3968 token.